Public funding of R&D and its effect on the composition of business R&D expenditure - Sergio Afcha; Guillén León López (BRQ Business Research Quarterly, 2014)
This paper discusses the potential effects of R&D public subsidies on a strategic issue for companies, the decision to combine internal and external R&D expenditure. Analyzing some arguments discussed in the management literature, it is assessed whether public intervention by granting R&D subsidies influences the composition of R&D expenditure. To do this, we analyze the data from the Survey on Business Strategies for the period 1991–2008. Results confirm that the public funding of R&D expenditure through subsidies have a positive impact on internal R&D and especially in the decision to conduct R&D internally and externally simultaneously."
Keywords: 650; Innovation strategy; Technology policy evaluation; R&D subsidies; Selection models; Internal–external R&D